2019
DOI: 10.1097/sle.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Congenital Gastric Outlet Obstruction due to a Web: A Retrospective Single-center Review

Abstract: Background: Congenital gastric antral web and congenital pyloric atresia are rare reasons of congenital gastric outlet obstruction (CGOO). Depending on the different forms, the symptoms vary from unspecific epigastric pain to nonbilious "projectile" vomiting, ileus and failure to thrive. Throughout the years, many different treatment options are described, like simple surgical dilatation, incision or excision of the membrane, possibly combined with a pyloroplasty.Patients and Methods: In this retrospective sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Six pediatric series in the English literature containing 78 cases were retrieved and compared ( 1 , 3 , 5 , 6 , 8 , 9 ) ( Table 4 ). In addition to the gender and diagnostic age, the onset-to-diagnosis and modalities of intervention were denoted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six pediatric series in the English literature containing 78 cases were retrieved and compared ( 1 , 3 , 5 , 6 , 8 , 9 ) ( Table 4 ). In addition to the gender and diagnostic age, the onset-to-diagnosis and modalities of intervention were denoted.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis can be challenging, given the non-specific symptoms and relatively insufficient awareness of this etiology ( 3 ). The inconsistency of episodic presentations and misinterpretation of the image may also puzzle the physicians ( 3 ). Partial obstruction may lead to a prolonged diagnostic process and inefficacious treatment ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] In recent years, several cases have shown that balloon dilatation combined with needle-knife incisions had low risk of perforation or significant bleeding and hence could also be a sufficient treatment modality. [ 5 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…High level of experience and suitable equipment is required. 10 Intraoperatively, it is important to exclude the presence of multiple diaphragms or atresias.…”
Section: Discussionmentioning
confidence: 99%